Genomic insights into the origin and diversification of late maritime hunter-gatherers from the Chilean Patagonia - de la Fuente, Constanza; Avila-Arcos, Mara C.; Galimany, Jacqueline; Carpenter, Meredith L.; Homburger, Julian R.; Blanco, Alejandro; Contreras, Paloma; Davalos, Diana Cruz; Reyes, Omar; San Roman Bontes, Manuel Julio; Moreno-Estrada, Andres; Campos, Paula F.; et al. (My University, 2018)
Patagonia was the last region of the Americas reached by humans who entered the continent from Siberia similar to 15,000-20,000 y ago. Despite recent genomic approaches to reconstruct the continental evolutionary history, regional characterization of ancient and modern genomes remains understudied. Exploring the genomic diversity within Patagonia is not just a valuable strategy to gain a better understanding of the history and diversification of human populations in the southernmost tip of the Americas, but it would also improve the representation of Native American diversity in global databases of human variation. Here, we present genome data from four modern populations from Central Southern Chile and Patagonia (n = 61) and four ancient maritime individuals from Patagonia (similar to 1,000 y old). Both the modern and ancient individuals studied in this work have a greater genetic affinity with other modern Native Americans than to any non-American population, showing within South America a clear structure between major geographical regions. Native Patagonian Kaweskar and Yamana showed the highest genetic affinity with the ancient individuals, indicating genetic continuity in the region during the past 1,000 y before present, together with an important agreement between the ethnic affiliation and historical distribution of both groups. Lastly, the ancient maritime individuals were genetically equidistant to a similar to 200-y-old terrestrial hunter-gatherer from Tierra del Fuego, which supports a model with an initial separation of a common ancestral group to both maritime populations from a terrestrial population, with a later diversification of the maritime groups.
Keywords: paleogenomics; patagonia; maritime hunter-gatherers